Egg‐white‐specific IgA and IgA2 antibodies in egg‐allergic children: Is there a role in tolerance induction?. Issue 1 (7th October 2013) - Konstantinou, George N.; Nowak‐Węgrzyn, Anna; Bencharitiwong, Ramon; Bardina, Luda; Sicherer, Scott H.; Sampson, Hugh A.
Abstract Background Decreased serum food‐specific IgA antibodies have been associated with allergic disease in cross‐sectional, case–control studies. The purpose of this study was to prospectively compare egg‐white‐(EW)‐specific IgA and IgA2 levels between egg‐allergic children and children tolerating egg. Methods Seventeen egg‐allergic children were followed prospectively. Total IgA, EW‐specific IgA, and EW‐specific IgA2 levels were measured in their sera with a sensitive ELISA. As negative controls were used children with no previous history of egg allergy. Egg‐allergic children with or without concomitant milk allergy were evaluated as additional controls with measurement of casein‐specific IgA. Results After 2.5 ± 0.9 yrs, nine out of the 17 allergic children became tolerant and eight remained allergic to baked egg. Baseline EW‐specific IgA2 levels were significantly lower in the egg‐allergic subjects (median 23.9 ng/ml) compared with the negative control subjects (99.4 ng/ml) and increased significantly by 28% over the study time period in eight out of the nine allergic children that became tolerant to baked egg. There was no significant change over time in EW‐specific IgA in any of the study groups. Non‐milk‐allergic subjects with concomitant egg allergy had almost threefold higher casein‐specific IgA levels than the milk‐ and egg‐allergic subjects (p = 0.025). Conclusions These results suggest a potential role for allergen‐specific IgA2 antibodies in the induction of food tolerance. Furthermore, they support the hypothesis that immature or impaired production of allergen‐specific IgA2 may be associated with the pathophysiology of food allergy, a defect that seems to be selective for the culprit allergen.